Composite current collector with foamed aluminum filled with carbon and preparation method and application of composite current collector
By filling the blended sodium chloride and polyacrylonitrile in the three-dimensional through-holes of the foam aluminum foam, and building a porous carbon structure through heat treatment, the problem of insufficient conductivity of the current collector of the foam aluminum foam aluminum foam is solved, and higher mechanical strength, lower contact resistance and better electrochemical performance are achieved, improving the performance and safety of the battery.
Patent Information
- Application Number
- CN202411888647.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The conductivity of existing foam aluminum positive electrode current collectors still needs to be improved, resulting in insufficient performance in applications with high energy density and high power density.
By blending sodium chloride and polyacrylonitrile, filling it in the three-dimensional through-hole of the foam aluminum foam, and building a porous carbon structure through two-stage heat treatment, the obtained composite fluid combines the three-dimensional porous structure of the foam aluminum foam and the high conductivity of the porous carbon.
It significantly improves the mechanical strength and structural stability of the material, reduces the contact resistance with the electrode material, improves the conductivity, improves the volume strain during the charging and discharging process, and improves the cycle stability and safety of the battery.
Smart Images

Figure CN119725554A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite current collector filled with carbon in foam aluminum and a preparation method and application thereof, belonging to the technical field of composite current collectors and preparation thereof. Background Art
[0002] Aluminum-based materials are widely used as current collector materials due to their excellent conductivity and lightweight properties. Traditional commercial aluminum-based current collector materials mainly include aluminum foil, carbon-coated aluminum foil and aluminum foam. However, these materials have certain limitations in performance, especially in applications with high energy density and high power density.
[0003] As the most basic current collector material, aluminum foil has good conductivity and cost-effectiveness. However, its surface is smooth, the contact area with the electrode material is limited, and during the battery charging and discharging process, aluminum foil cannot effectively buffer the volume change, resulting in a decrease in battery performance.
[0004] Carbon-coated aluminum foil is made by coating a layer of carbon material on the surface of aluminum foil, which improves the conductivity of the current collector and the adhesion with the electrode material, reduces the internal resistance of the battery, and improves the rate performance and cycle stability of the battery. However, the preparation process of carbon-coated aluminum foil is relatively complicated, and the uniformity and stability of the carbon layer are still technical challenges.
[0005] Foamed aluminum provides a larger specific surface area and better electrochemical performance with its three-dimensional porous structure, but it has a large porosity, low mechanical strength, and is prone to forming an oxide film in the air, resulting in poor contact with electrode materials and high resistance, which is not conducive to improving the power density of the device, and its conductive performance still needs to be improved. Summary of the invention
[0006] In order to solve the problem that the conductivity of the existing foam aluminum positive electrode current collector still needs to be improved, the present invention provides a composite current collector filled with carbon in foam aluminum, and a preparation method and application thereof.
[0007] The technical solution of the present invention:
[0008] One of the purposes of the present invention is to provide a method for preparing a composite current collector filled with carbon in foamed aluminum, the method comprising the following steps:
[0009] (1) mixing sodium chloride and polyacrylonitrile and then subjecting them to ball milling to obtain a mixed powder with uniform mixing and fine particles;
[0010] (2) placing the foamed aluminum with three-dimensional through holes in a graphite mold, filling it with mixed powder, and covering it with a graphite mold cover with threads and exhaust holes;
[0011] (3) placing the graphite mold as a whole into a tubular furnace, introducing flowing protective gas, performing two-stage heat preservation treatment, and then naturally cooling to room temperature to obtain a foamed aluminum / carbon composite;
[0012] (4) Using water to dissolve and remove the sodium chloride in the foamed aluminum / carbon composite to obtain a porous integrated composite current collector.
[0013] It is further defined that the mass ratio of sodium chloride to polyacrylonitrile in (1) is 1:(1-1000).
[0014] It is further defined that the particle size of the mixed powder obtained in (1) is 0.1 to 100 μm.
[0015] It is further defined that the protective gas in (3) is argon.
[0016] It is further defined that the first insulation zone of the two-stage insulation in (3) is 320-400°C and the time is 2h.
[0017] It is further defined that the second insulation zone of the two-stage insulation in (3) is 600-650°C and the time is 3 hours.
[0018] It is further defined that the heating rate from the first insulation zone to the second insulation zone in the two-stage insulation in (3) is 2 to 10°C / min.
[0019] A second object of the present invention is to provide a composite current collector prepared by the above method.
[0020] It is further defined that the composite current collector is composed of foamed aluminum and a porous carbon structure filled in the three-dimensional through holes of the foamed aluminum.
[0021] The third object of the present invention is to provide an application of the above-mentioned composite current collector, specifically for preparing a positive electrode sheet for a lithium ion battery, a lithium sulfur battery or a sodium ion battery.
[0022] Beneficial effects of the present invention:
[0023] The present invention uses sodium chloride as a template agent, blends it with polyacrylonitrile and fills it in the three-dimensional through holes of foam aluminum. After staged heat treatment, water is used to dissolve the sodium chloride, and a porous carbon structure is constructed in the three-dimensional through holes of the foam aluminum. The obtained composite current collector combines the three-dimensional porous structure of the foam aluminum and the high conductivity of the porous carbon. While significantly improving the mechanical strength of the material and enhancing the structural stability of the current collector, the continuous porous carbon structure effectively reduces the contact resistance between the current collector material and the electrode material, and improves the conductivity. In addition, the rich pore structure of the current collector also effectively improves the volume strain of the current collector during the charge and discharge process, and improves the cycle stability and safety of the battery.
[0024] In summary, the composite current collector prepared by the present invention has higher mechanical strength, lower contact resistance and better electrochemical performance than existing commercial aluminum-based current collector materials. It has significant advantages in improving battery performance and safety, and is expected to play an important role in high energy density and high power density battery technology.
[0025] In addition, the present invention uses sodium chloride as a template, and can stably prepare a composite current collector with rich pore structure and high conductivity at low cost, and can also adjust the pore structure according to the filling amount and particle size of sodium chloride. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The SEM images of the composite current collector prepared in Example 1 (different magnifications);
[0027] Figure 2 The cycle performance diagram of the lithium ion battery assembled with the positive electrodes prepared in Example 1 and Comparative Example 1;
[0028] Figure 3 The cycle performance diagram of the lithium-sulfur battery assembled with the positive electrodes prepared in Example 2, Comparative Example 2 and Comparative Example 3;
[0029] Figure 4 This is a comparison chart of the resistivity of the positive electrode sheets prepared in Example 2, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0032] Example 1
[0033] The method for preparing the foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0034] (1) Weigh 100 g of sodium chloride and 200 g of polyacrylonitrile (polyacrylonitrile molecular weight is 25000-80000), add them into a ball mill for ball milling, the specific ball milling power is 1 kW, the ball milling time is 1 h, and a sodium chloride / polyacrylonitrile mixed powder with uniform mixing and fine particles and a particle size of 20 μm is obtained.
[0035] (2) A three-dimensional through-hole aluminum foam (purchased from Fuershun Electronic Materials Co., Ltd., model PPI-90) with a size of 10 cm × 10 cm × 1 mm was placed in a graphite mold, and the above-obtained sodium chloride / polyacrylonitrile mixed powder was evenly filled (specifically 1 g), and covered with a graphite mold cover with threads and vents.
[0036] (3) The filled and tightly covered graphite mold is placed in a tubular furnace, argon is introduced as a protective gas, and the mold is first heated to 325°C and kept at this temperature for 2 h, then heated to 650°C at a heating rate of 2°C / min and kept at this temperature for 3 h, and then cooled to room temperature.
[0037] (4) The aluminum foam / carbon composite obtained after cooling was soaked in water for 1 hour to dissolve and remove the sodium chloride, thereby obtaining an aluminum foam / carbon composite porous integrated current collector, which was then dried in a 60° C. forced air drying oven for later use.
[0038] The method for preparing the positive electrode sheet using the above-mentioned foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0039] Step 1: Mix and homogenize the positive electrode active material LiMnFePO4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry;
[0040] Step 2: Coat the positive electrode material slurry prepared in step 1 on the cut and welded aluminum tab foamed aluminum / carbon composite porous integrated current collector prepared in Example 1, oscillate until the slurry is completely filled and dry in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0041] In this embodiment, the positive electrode sheet prepared above is used to assemble a lithium-ion battery with a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-275).
[0042] Comparative Example 1
[0043] The method for preparing the current collector in this comparative example is as follows:
[0044] (1) A three-dimensional through-hole aluminum foam (purchased from Fuershun Electronic Materials Co., Ltd., model number PPI-90) with a size of 10 cm × 10 cm × 1 mm was placed into a graphite mold and covered with a graphite mold cover with threads and vent holes.
[0045] (2) The filled and tightly covered graphite mold was placed in a tubular furnace, argon was introduced as a protective gas, and the mixture was first heated to 325°C and kept at this temperature for 2 h, then heated to 650°C at a heating rate of 2°C / min and kept at this temperature for 3 h, and then cooled to room temperature.
[0046] The method for preparing the positive electrode sheet using the above current collector in this comparative example is as follows:
[0047] Step 1: Mix and homogenize the positive electrode active material LiMnFePO4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry;
[0048] Step 2: Coat the positive electrode material slurry prepared in step 1 on the current collector prepared in comparative example 1 which has been cut and welded with aluminum tabs, oscillate until the slurry is completely filled, and then dry in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0049] In this comparative example, a lithium-ion battery is assembled using the positive electrode sheet prepared above, a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-275).
[0050] Example 2
[0051] The method for preparing the foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0052] (1) Weigh 100 g of sodium chloride and 1000 g of polyacrylonitrile, add them into a ball mill for ball milling, the specific ball milling power is 1 kW, the ball milling time is 1 h, and a sodium chloride / polyacrylonitrile mixed powder with uniform mixing and fine particles and a particle size of 10 μm is obtained.
[0053] (2) A three-dimensional through-hole aluminum foam (purchased from Fuershun Electronic Materials Co., Ltd., model PPI-90) with a size of 10 cm × 10 cm × 1 mm was placed in a graphite mold, and the above-obtained sodium chloride / polyacrylonitrile mixed powder was evenly filled (specifically 1 g), and covered with a graphite mold cover with threads and vents.
[0054] (3) The filled and tightly covered graphite mold was placed in a tubular furnace, argon was introduced as a protective gas, and the mold was first heated to 330°C and kept at this temperature for 2 h, then heated to 650°C at a heating rate of 5°C / min and kept at this temperature for 3 h, and then cooled to room temperature.
[0055] (4) The aluminum foam / carbon composite obtained after cooling was soaked in water for 1 hour to dissolve and remove the sodium chloride to obtain an aluminum foam / carbon composite porous integrated current collector, which was then dried in a 60° C. forced air drying oven for later use.
[0056] The method for preparing the positive electrode sheet using the above-mentioned foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0057] Step 1: Mix and homogenize the positive electrode active material S8 / carbon composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry;
[0058] Step 2: Coat the positive electrode material slurry prepared in step 1 on the cut and welded aluminum tab foamed aluminum / carbon composite porous integrated current collector prepared in Example 2, oscillate until the slurry is completely filled and dry in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0059] In this embodiment, a lithium-sulfur battery is assembled using the positive electrode sheet prepared above, a metal lithium negative electrode and a lithium-sulfur battery secondary electrolyte (1MLiTFSI / DOL-DME (v / v=1:1)).
[0060] Comparative Example 2
[0061] The method for preparing the current collector in this comparative example is as follows:
[0062] (1) A three-dimensional through-hole aluminum foam (purchased from Fuershun Electronic Materials Co., Ltd., model PPI-90) with a size of 10 cm×10 cm×1 mm was placed in a graphite mold and covered with a graphite mold cover with threads and vent holes.
[0063] (2) Place the filled and tightly covered graphite mold into a tubular furnace, introduce argon as a protective gas, first heat to 330°C and keep it warm for 2 hours, then heat to 650°C at a heating rate of 5°C / min and keep it warm for 3 hours, then cool to room temperature to obtain a current collector for use.
[0064] The method for preparing the positive electrode sheet using the above current collector in this comparative example is as follows:
[0065] Step 1: Mix and homogenize the positive electrode active material S8 / carbon composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry;
[0066] Step 2: Coat the positive electrode material slurry prepared in step 1 on the foamed aluminum / carbon composite porous integrated current collector prepared in comparative example 2 after cutting and welding with aluminum tabs, and after shaking until the slurry is completely filled, dry it in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0067] In this embodiment, the positive electrode sheet prepared above is used to assemble a lithium-sulfur battery with a metal lithium negative electrode and a lithium-sulfur battery secondary electrolyte (LS-001).
[0068] Comparative Example 3
[0069] The method for preparing the current collector in this comparative example is as follows:
[0070] (1) Place a carbon-coated aluminum foil with a size of 10 cm × 10 cm × 1 mm into a graphite mold and cover it with a graphite mold cover with threads and vent holes.
[0071] (2) Place the filled and tightly covered graphite mold into a tubular furnace, introduce argon as a protective gas, first heat to 350°C and keep it for 2 hours, then heat to 655°C at a heating rate of 5°C / min and keep it for 3 hours, then cool to room temperature to obtain a current collector for use.
[0072] The method for preparing the positive electrode sheet using the above current collector in this comparative example is as follows:
[0073] Step 1: Mix and homogenize the positive electrode active material S8 / carbon composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry;
[0074] Step 2: Coat the positive electrode material slurry prepared in step 1 on the foamed aluminum / carbon composite porous integrated current collector prepared in comparative example 2 after cutting and welding with aluminum tabs, and after shaking until the slurry is completely filled, dry it in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0075] In this embodiment, the positive electrode sheet prepared above is used to assemble a lithium-sulfur battery with a metal lithium negative electrode and a lithium-sulfur battery secondary electrolyte (LS-001).
[0076] Example 3
[0077] The method for preparing the foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0078] (1) Weigh 100 g of sodium chloride and 500 g of polyacrylonitrile, add them into a ball mill for ball milling, the specific ball milling power is 1 kW, the ball milling time is 1 h, and a sodium chloride / polyacrylonitrile mixed powder with uniform mixing and fine particles and a particle size of 20 μm is obtained.
[0079] (2) A three-dimensional through-hole aluminum foam (purchased from Fuershun Electronic Materials Co., Ltd., model PPI-90) with a size of 10 cm × 10 cm × 1 mm was placed in a graphite mold, and the above-obtained sodium chloride / polyacrylonitrile mixed powder was evenly filled (specifically 1 g), and covered with a graphite mold cover with threads and vents.
[0080] (3) The filled and tightly covered graphite mold was placed in a tubular furnace, argon was introduced as a protective gas, and the mold was first heated to 350°C and kept at this temperature for 2 h, then heated to 655°C at a heating rate of 5°C / min and kept at this temperature for 3 h, and then cooled to room temperature.
[0081] (4) Soaking the aluminum foam / carbon composite obtained after cooling in water for 60 minutes to dissolve and remove sodium chloride to obtain an aluminum foam / carbon composite porous integrated current collector, which is then dried in a 60° C. forced air drying oven for later use.
[0082] The method for preparing the positive electrode sheet using the above-mentioned foam aluminum / carbon composite porous integrated current collector in this embodiment is as follows:
[0083] Step 1: Mix and homogenize the positive electrode active material Na3V2(PO4)3 with the conductive agent acetylene black, the C45 carbon black conductive agent, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution in a mass ratio of 93.5:1.5:1.5:3.5 to obtain a positive electrode material slurry;
[0084] Step 2: Coat the positive electrode material slurry prepared in step 1 on the cut and welded aluminum tab foamed aluminum / carbon composite current collector prepared in Example 3, oscillate until the slurry is completely filled, and then dry in an oven at 100° C. for 12 hours to obtain a positive electrode sheet.
[0085] In this embodiment, a sodium ion battery is assembled using the positive electrode sheet prepared above, a metallic sodium negative electrode and a sodium ion secondary electrolyte (NP-005).
[0086] Effect example
[0087] (1) The microscopic morphology of the composite current collector prepared in Example 1 was characterized. The results are as follows: Figure 1 As shown. Figure 1 It can be seen from a that the polyacrylonitrile carbon material after removing the sodium chloride template is evenly filled in the three-dimensional network structure of the foamed aluminum. Figure 1 b further shows that the particle size of the carbon material is about 50 nm and the pores are evenly distributed, which provides space for the subsequent uniform filling of active substances.
[0088] (2) The cycle performance of the batteries prepared in Examples 1 and 2 and Comparative Examples 1 to 3 were tested and compared. The results are as follows: Figure 2 and 3 As shown. Figure 2 It can be seen that the initial capacity of the battery assembled in Example 1 is 110 mAh g -1 After 1000 cycles at 5C current density, there is still 58 mAh g -1 The discharge capacity of Comparative Example 1 is 85 mAh g -1 After 1000 cycles at 5C current density, the capacity decay is 39 mAh g -1 Therefore, it is shown that the composite current collector prepared in Example 1 has a better discharge capacity retention rate. Figure 3 It can be seen that when the foamed aluminum / carbon composite current collector prepared in Example 2 is used as the positive electrode of a lithium-sulfur battery, its initial discharge capacity is 1001 mAh g at a current density of 0.2C. -1 After 200 cycles, the discharge capacity remained at 578 mAh g -1, while the initial discharge capacity of Comparative Examples 2 and 3 is 789 mAh g -1 and 553mAh g -1 The discharge capacity after 200 cycles is 555 mAh g -1 and 350mAh g -1 By comparison, it can be seen that the composite current collector prepared in Example 2 can stimulate the high activity of the positive electrode material of the lithium-sulfur battery and provide a higher discharge capacity.
[0089] (3) The resistivity of the positive electrode sheets prepared in Example 2 and Comparative Examples 2 and 3 was characterized, and the comparison results were as follows: Figure 4 As shown in the figure, it can be seen that the resistivity of the foam positive electrode sheet prepared in Example 2 is 46Ω·μm, and the resistivity of the positive electrode sheet of Comparative Example 2 and the positive electrode sheet of Comparative Example 3 are 58Ω·μm and 86Ω·μm, respectively. By comparison, it can be seen that the positive electrode sheet prepared in Example 2 has a smaller resistivity, which is beneficial to the rate discharge performance of the electrode sheet and reduces the energy loss caused by its own resistance.
[0090] In summary, the composite current collector provided by the present invention can significantly improve the discharge capacity and cycle life of the battery when used in a lithium ion or sodium ion battery, and effectively improves the rate performance of the electrode.
[0091] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a composite current collector, characterized in that: include: (1) mixing sodium chloride and polyacrylonitrile and then subjecting them to ball milling to obtain a mixed powder with uniform mixing and fine particles; (2) placing the foamed aluminum with three-dimensional through holes in a graphite mold, filling it with mixed powder, and covering it with a graphite mold cover with threads and exhaust holes; (3) placing the graphite mold as a whole into a tubular furnace, introducing flowing protective gas, performing two-stage heat preservation treatment, and then naturally cooling to room temperature to obtain a foamed aluminum / carbon composite; (4) Using water to dissolve and remove the sodium chloride in the foamed aluminum / carbon composite to obtain a porous integrated composite current collector.
2. The preparation method according to claim 1, characterized in that: (1) The mass ratio of sodium chloride to polyacrylonitrile is 1:(1-1000).
3. The preparation method according to claim 1, characterized in that: (1) The particle size of the obtained mixed powder is 0.1 to 100 μm.
4. The preparation method according to claim 1, characterized in that: (3) The protective gas is argon.
5. The preparation method according to claim 1, characterized in that: (3) The first insulation zone of the two-stage insulation is 320-400℃, and the time is 2h.
6. The preparation method according to claim 1, characterized in that: (3) The second insulation zone of the two-stage insulation is 600-650℃, and the time is 3h.
7. The preparation method according to claim 1, characterized in that: (3) The heating rate from the first insulation zone to the second insulation zone in the two-stage insulation is 2 to 10°C / min.
8. A composite current collector prepared by the method according to any one of claims 1 to 7.
9. The composite current collector according to claim 8, characterized in that: The composite current collector consists of foam aluminum and a porous carbon structure filled in the three-dimensional through holes of the foam aluminum.
10. An application of the composite current collector according to claim 8, characterized in that: Used to prepare positive electrode sheets for lithium-ion batteries, lithium-sulfur batteries or sodium-ion batteries.
Citation Information
Patent Citations
Zinc electrode for zinc / air battery and preparation method of zinc electrode
CN106898725A
A method for preparing a high specific capacity nanocomposite material by using a dual template
CN109243853A
Preparation method for graphene reinforced aluminum matrix composite foam material
CN109317690A
Positive plate, preparation method of positive plate, battery, preparation method of battery and electric equipment
CN118039807A
Foamed aluminum positive electrode current collector and preparation method and application thereof
CN118367155A